Optimization and Modeling of Tetracycline Removal from Wastewater by Three-Dimensional Electrochemical System: Application of Response Surface Methodology and Least Squares Support Vector Machine - Foroughi, Maryam; Rahmani, Ali Reza; Asgari, Ghorban; Nematollahi, Davood; Yetilmezsoy, Kaan; Samarghandi, Mohammad Reza (SPRINGER, 2020)
A three-dimensional electrochemical system was employed as an advanced treatment technology for treatment of tetracycline-containing wastewater. An initial tetracycline concentration of 20.17-100.23 mg/L, pH range of 2.43-9.18, and current density of 1.03-15.72 mA/cm(2) were implemented for the optimization and modeling of the process within the framework of a three-factor, five-level Box-Wilson central composite design-based response surface methodology and least squares support vector machine. The results of statistics corroborated that three main effective factors and reactor performance were very well described by the second-order polynomial equation (coefficient of determination = 0.94, mean square error = 0.0042, root mean square error = 0.065, average absolute deviation = 2.51, and mean absolute error = 0.037). Under the optimal conditions introduced by the desirability function approach, 90.42 (+/- 2.3)%, 49.91 +/- (8.4)% and 28.80 +/- (16.70)% of tetracycline, chemical oxygen demand, and total organic carbon could be removed using the three-dimensional electrochemical process from wastewater. The findings of this study demonstrated that the three-dimensional electrochemical system was as an effective, simple, and economic process compared to other electrochemical systems that have been recently used for antibiotics removal and could be considered as a promising technology for further investigations.
Keywords: Antibiotic; Tetracycline; Central composite design; Three-dimensional electrochemical system; Support vector machine; Modeling; ANODIC-OXIDATION; ANTIBIOTIC TETRACYCLINE; EXPERIMENTAL-DESIGN; ACTIVATED CARBON; ADSORPTION; ELECTRODE; ELECTROCOAGULATION; DEGRADATION; PHARMACEUTICALS; CONTAMINANTS; Environmental Sciences & Ecology